Sports activities during any pandemic lockdown - Lim, M. A.; Pranata, R. (Irish Journal of Medical Science, 2020)
The coronavirus disease 2019 (COVID-19) pandemic forced the world`s population to alter daily routines, including exercise habits. This unusual situation has physical, psychological, and behavioral consequences to all individuals, including elite and recreational athletes. Life in lockdown has been difficult because everyone has to stay safe and healthy, while at the same time abiding by new norms. Currently, mitigation strategies have been widely implemented to contain the spread of COVID-19. These measures include lockdown, social distancing, personal protective measures, and environmental and surface cleaning [1]. Furthermore, the practice of physically active lifestyles is recommended to counteract health and mental consequences of the COVID-19 pandemic [2]. While sedentary behavior certainly has no effect on the immunity, exercising in moderation is associated with improved immune competency and a reduced risk of illness. Overtraining and high-intensity exercise induce transient immune dysfunction and are associated with a greater risk of illness, including upper respiratory tract infections, but this may not apply to elite sportsmen. With insights for athletes,healthy individuals, and high-riskindividuals (problems causedby theCOVID-19 pandemic, consequences of physical inactivity or detraining, goals durinlockdown,isolation, and quarantine, health risks for returning to normal activities during COVID-19, recommendations for transitioning to normal activities during COVID-19).